Impact of an arbuscular mycorrhizal fungal inoculum and exogenous methyl jasmonate on the performance of tall fescue under saline-alkali condition - Liu, Hui; Tang, Huimin; Ni, Xiaozhen; Zhang, Yajie; Wang, Yingchao (Frontiers in Microbiology, 2022)
Hormonal regulation and symbiotic relationships provide benefits for plants to overcome stress conditions. The aim of this study was to elucidate the effects of arbuscular mycorrhizal fungal (AMF) inoculum, methyl jasmonate (MeJA) and saline-alkali effects on the growth and physiology of tall fescue (Festuca elata ‘Crossfire II’). Treatments included AMF-inoculation, and non-AMF inoculation, four MeJA application concentrations (0, 50, 100, 200 mg/L) and two saline-alkali levels (0 and 200 mmol/L). The results showed that AMF inoculation significantly enhanced saline-alkali resistance of the plants, and the beneficial effects were increased by MeJA at a concentration of 50 mg/L (50 MeJA) and decreased by MeJA at a concentration both of 100 (100 MeJA) and 200 mg/L (200 MeJA). AMF inoculation plants when treated with 50 MeJA accumulated significantly more biomass, had greater proline and total phenolic concentration, and lower malondialdehyde (MDA) concentration than plants only treated either with AMF or 50 MeJA. However, no significant differences of growth or physiological characters were observed between AMF and non-AMF plants when treated either with 100 or 200 MeJA. All of these results suggest the interaction between a certain concentration of MeJA and AMF can significantly increase saline-alkali resistance of the tall fescue by regulating the biomass, proline, total phenolic and MDA. Our findings provide new information on the effect of biological and chemical priming treatments for plant performance under saline-alkali stress.